2016
DOI: 10.1515/npf-2015-0051
|View full text |Cite
|
Sign up to set email alerts
|

Governing Civil Society in Nigeria and Zimbabwe: A Question of Policy Process and Non-State Actors’ Involvement

Abstract: Sovereign nations have the right to regulate the activities and operations of civil society organizations (CSOs) within their jurisdiction. The nature of official policy controls bears important implications for the breath and health of associational life, to the degree that they are relaxed, restrictive, or intrusive. Since nations in Africa have often been seen to subvert the growth and impact of CSOs, this article traces the policy controls that govern CSOs in Nigeria and Zimbabwe. Within the context of pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The study was initially motivated by our interest in verifying how the most recent ACF applications have addressed the research agenda proposed in 2014 and reinforced in 2018. During our study, however, we noted an almost total lack of Latin American works covered by recent reviews, with only one Brazilian study identified (CARVALHO, 2001). In 2015, however, a group of Brazilian authors promoted a review of the use of ACF in Brazilian theses and dissertations and found 23 applications of the model published between 2010 and 2013 (CAPELARI; ARAÚJO; CALMON, 2015).…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…The study was initially motivated by our interest in verifying how the most recent ACF applications have addressed the research agenda proposed in 2014 and reinforced in 2018. During our study, however, we noted an almost total lack of Latin American works covered by recent reviews, with only one Brazilian study identified (CARVALHO, 2001). In 2015, however, a group of Brazilian authors promoted a review of the use of ACF in Brazilian theses and dissertations and found 23 applications of the model published between 2010 and 2013 (CAPELARI; ARAÚJO; CALMON, 2015).…”
Section: Introductionmentioning
confidence: 86%
“…Sabatier and Weible (2007) argue, however, that its objective is much greater, because the model should make it possible to understand the belief system of the coalitions and their relationship with policy change. The predominance of studies of a descriptive nature shows that the ACF is still often used to identify coalitions and describe how their actions influence the policy process (BARNES; VAN LAERHOVEN;DRIESSEN, 2016;CHIKOTO-SCHULTZ;UZOCHUKWU, 2016;MCDONALD;GALLAGHER, 2015), without, however, establishing the causal relationships between the model's categories.…”
Section: Research Methodologies Adopted In Applications Of the Acfmentioning
confidence: 99%
See 1 more Smart Citation